Improved Visualization of Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae)—Part II: Alimentary Canal Components and Measurements - Tawni L. Crippen; Jesus F. Esquivel (Psyche: A Journal of Entomology)
Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae) is a pest of stored food products and problematic to every type of poultry production facility. Larvae and adults can ingest and harbor foodborne and poultry pathogens. Determining the efficiency of this insect’s capacity to transmit disease is critical to improving management of A. diaperinus on poultry facilities and providing a safe food supply for human consumption. However, a deficiency exists in the literature reporting measurements of the gut and its defined segments. Previous reports include line drawing depictions, which aid little in the determination of the pathogen reservoir potential of these insects. Advances in technology allowed more accurate visualization and precise measurement of gross anatomical features of the alimentary canal. A photographic depiction to aid the researcher in the visualization of anatomical features and accurate measurements of the alimentary canal for these insects is presented here.